A Pressure Self‐Adaptable Route for Uniform Lithium Plating and Stripping in Composite Anode. (23rd October 2020) - Shi, Peng; Zhang, Xue‐Qiang; Shen, Xin; Li, Bo‐Quan; Zhang, Rui; Hou, Li‐Peng; Zhang, Qiang
Abstract: Lithium (Li) metal anode confronts impressive challenges to revolutionize the current rechargeable batteries due to the intractably unstable interface. The composite Li anode is proposed to relieve volume fluctuations and suppress Li dendrites apparently. However, the inner space of composite anodes still affords feasibility for the continuous growth of unconstrained Li dendrites, leading to a low utilization of deposited Li and even safety hazards. Herein, an emerging and rational strategy to design composite anodes is proposed to regulate the inner Li plating/stripping. The self‐adaptable pressure is generated by the filled elastic polymer inside conductive hosts, surpassing the yield strength of Li and confining Li to form a smooth morphology with a high utilization owing to the persistent electronic pathways under pressure. The pressure self‐adaptable composite anode renders 160 cycles with a capacity retention of 80% in comparison to 60 cycles with a planar Li under practical conditions. Moreover, a 1.0 Ah pouch cell undergoes 68 cycles impressively. This work not only presents a fresh perspective on regulation of inner Li plating/stripping by introducing a self‐adaptable pressure into the composite anode, but also demonstrates the avenue of exploring multifunctional composite anodes for practical Li metal batteries. Abstract : A pressure self‐adaptable strategy is proposed to regulate the inner Li plating/stripping in a composite anode. The intrinsic self‐adaptable pressure originates from the deformation of the polymer chains that is filled into the host pores during repeated cycles and can self‐adjust accompanied by the capacity changing.